A Caenorhabditis elegans Homologue of LYST Functions in Endosome and Lysosome‐Related Organelle Biogenesis. (24th February 2016) - Barrett, Alec; Hermann, Greg J.
Abstract : LYST‐1 is a Caenorhabditis elegans BEACH domain containing protein (BDCP) homologous to LYST and NBEAL2, BDCPs controlling organelle biogenesis that are implicated in human disease. Unlike the three other BDCPs encoded by C. elegans, mutations in lyst‐1 lead to smaller lysosome‐related organelles (LROs), smaller lysosomes, increased numbers of LROs and decreased numbers of early endosomes. lyst‐1(−) mutations do not obviously disrupt protein trafficking to lysosomes or LROs, however, the formation of gut granules is diminished.